Hormone manipulation to overcome a major barrier in male catfish spawning: The role of oxytocin augmentation in inducing voluntary captive spawning. (9th September 2020) - Priyadarshi, Himanshu; Das, Rekha; Singh, Atom Arun; Patel, Arun Bhai; Pandey, Pramod Kumar
Abstract: A major challenge in Clariid catfish seed production is our inability to induce voluntary captive spawning of the brooders. Since voluntary captive spawning had been previously elicited in a Clarias species by simulating natural breeding environment, we speculated that the major obstacle in voluntary spawning might be the absence of an inducing agent that triggers mating response in the brooders. To address the issue, oxytocin was injected to the brooders along with Ovatide (a commercial inducing agent comprising salmon gonadotropin‐releasing hormone analogue and domperidone). Administration of 40 mIU/kg body weight of oxytocin after 12 hr of Ovatide injection resulted in voluntary spawning of the fish (81.5%, i.e. 31 out of 38 trials), with more than 70% hatching rate in simple and low‐cost spawning facilities. Histology of male gonads indicated sustained gamete maturation and the gonads were observed to be visibly turgid in the fish that received both the hormones. In contrast, gamete maturation slackened after 10 hr in the control fish, injected with Ovatide only. Administration of oxytocin along with Ovatide was also observed to induce aggressive sexual behaviour among the males. Neither of the hormones, acting alone, could induce voluntary spawning in the fish or influence sexual behaviour. Our results clearly show that oxytocin plays a significant role in sustaining the male gamete maturation induced by Ovatide and trigger the behavioural mating response, leading to voluntary spawning in C. magur . The results hold potential to make a paradigm shift in the commercial catfish seed production technology.